2015
DOI: 10.5455/bcp.20130408021434
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Depression and Impulsivity on Obesity and Binge Eating Disorder

Abstract: Objective: The aim of study was to evaluate depression and impulsivity in obese people with binge eating disorder (BED). Method:The study included 149 obese study participants who were compared to 151 non-obese healthy controls. They were assessed with the Structured Clinical Interview (SCID-I), Eating Attitudes Test (EAT), Beck Depression Inventory (BDI), and Barratt Impulsiveness Scale-11 (BIS-11). Results:The prevalence of BED was 47.6% in the obese study participants. Obesity with BED was more common in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Overweight and obese individuals are also at high risk of suicide, but data on the role of BED in predicting suicide risk in this clinical population are inconsistent, as the samples examined by the studies reviewed herein were too small to be statistically significant (Jenkins et al, 2002 ; Annagur et al, 2015 ; Fichter and Quadflieg, 2016 ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Overweight and obese individuals are also at high risk of suicide, but data on the role of BED in predicting suicide risk in this clinical population are inconsistent, as the samples examined by the studies reviewed herein were too small to be statistically significant (Jenkins et al, 2002 ; Annagur et al, 2015 ; Fichter and Quadflieg, 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…Among the studies investigating the associations between suicidality and BED, seven papers (Ackard et al, 2003 , 2011 ; Swanson et al, 2011 ; Carano et al, 2012 ; Izydorczyk and Mazur, 2012 ; Portzky et al, 2014 ; Forrest et al, 2017 ) reported data on SI, whereas 16 papers reported data on SA and suicide completion in individuals with BED (Ackard et al, 2003 , 2011 ; Grucza et al, 2007 ; Chen et al, 2008 ; McElroy et al, 2011 , 2016 ; Swanson et al, 2011 ; Carano et al, 2012 ; Izydorczyk and Mazur, 2012 ; Pisetsky et al, 2013 ; Portzky et al, 2014 ; Runfola et al, 2014 ; Suokas et al, 2014 ; Annagur et al, 2015 ; Forrest et al, 2017 ; Welch et al, 2016 ). By examining the results of these studies, it was observed that the prevalence of SI varied between 26.3% (Ackard et al, 2003 ) and 51.7% (Portzky et al, 2014 ), and that the rates of SA and suicide completion varied between 2.3% (Suokas et al, 2014 ) and 34% (McElroy et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth stressing that among people with excessive body mass, a high percentage (from 10 to 47.6%) are individuals with binge eating disorder (BED) and with bulimia [ 15 , 55 57 ], but as mentioned earlier, eating disorders are also common in individuals with normal weight [ 6 , 53 ]. There are many theories that emphasise the importance of emotions in eating disorders and persistence of excessive weight (including Emotional Reward Theory, Emotion Avoidance Model) [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%